ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Accurate and rapid nucleic acid detection is vital for the early diagnosis of infectious diseases. Conventional polymerase chain reaction (PCR) offers high sensitivity but is hindered by bulky equipment, long processing times, and the need for technical expertise, limiting its point-of-care testing (POCT) applications. To overcome these constraints, we developed an innovative photonic PCR system utilizing the plasmonic photothermal effect of a gold nanofilm to accelerate the amplification process. This system integrates a lateral flow assay (LFA) for the streamlined visual detection of FITC- and biotin-labeled Seoul orthohantavirus (SEOV) amplicons using gold nanoparticle-conjugated antibodies. By synergizing photonic PCR with LFA, we achieved real-time-like detection of target products within 15 min (excluding the extraction step). This integrated platform demonstrates a limit of detection (LOD) of 150 copies/mL of the template genome, significantly enhancing diagnostic sensitivity. Our design prioritizes simplicity and efficiency, eliminating the requirement for sophisticated instrumentation or extensive operator training. Given its rapid processing, cost-effectiveness, and high sensitivity, this photonic PCR-LFA system represents a compelling solution for diverse diagnostic applications, including clinical diagnostics, environmental monitoring, and field-based testing. This advancement underscores the potential of plasmon-driven materials in transforming next-generation molecular POCT platforms.